A complex health services intervention to improve medical care in long-term care homes: study protocol of the controlled coordinated medical care (CoCare) study - Boris A. Brühmann; Christina Reese; Klaus Kaier; Margrit Ott; Christoph Maurer; Simone Kunert; Bruno R. Saurer; Erik Farin (BMC, 2019)
Abstract Background Deficits in general and specialized on-site medical care are a common problem in nursing homes and can lead to unnecessary, costly and burdensome hospitalizations for residents. Reasons for this are often organizational obstacles (such as lack of infrastructure or communication channels) and unfavorable compensation structures, which impede the implementation of adequate medical care. The purpose of this study is to evaluate a complex intervention aiming to improve the coordination of medical care in long-term care nursing homes in Germany. The project aims to optimize the collaboration of nurses and physicians in order to reduce avoidable hospital admissions and ambulance transportations. Methods/design In a prospective controlled trial, nursing home residents receiving a complex on-site intervention are compared to residents receiving care/treatment as usual. The study will include a total of around 4000 residents in approximately 80 nursing homes split equally between the intervention group and the control group. Recruitment will take place in all administrative districts of Baden-Wuerttemberg, Germany. The control group focuses on the administrative district of Tuebingen. The intervention includes on-site visits by physicians joined by nursing staff, the formation of teams of physicians, a computerized documentation system (CoCare Cockpit), joint trainings and audits, the introduction of structured treatment paths and after-hours availability of medical care. The project evaluation will be comprised of both a formative process evaluation and a summative evaluation. Discussion This study will provide evidence regarding the efficacy of a complex intervention to positively influence the quality of medical care and supply efficiency as well as provide cost-saving effects. Its feasibility will be evaluated in a controlled inter-regional design. Trial registration WHO UTN: U1111-1196-6611; DRKS-ID: DRKS00012703 (Date of Registration in DRKS: 2017/08/23).